Calitatea vieții ca obiectiv politic - Zamfir, Cătălin (Calitatea Vieții, 1990)
The study brings to our attention the problem of QL as an objective of collective and individual action. The first section contains considerations supporting the idea that, particularly under the present conditions of Romania, the QL goal requires a systematic pursuit. A coherent QL policy is needed: The second section reveals five paradoxes of the action directed towards the improvement of QL. The final section deals with the possibility of developing a coherent QL policy under the present conditions of Romania, and it shows the directions inviting for action.